Beauty and the beast [videorecording (DVD)] - Watson, Emma, 1990-; Stevens, Dan, 1982-; Evans, Luke, 1979-; Kline, Kevin (Disney DVD., 2017)
The fantastic journey of Belle, a bright and independent young woman who takes her father's place as the prisoner of a beast in his castle. As Belle befriends the castle's enchanted staff, she and the Beast slowly begin to look beyond their initial reactions to each other and see who they truly are. But back in Belle's village, her father's fears for her safety drive him to rally the villagers to free Belle from the castle--a plan that goes awry, with dangerous consequences, when Belle's would-be suitor Gaston twists the rally into a mob and leads an attack on the castle.